Clinicopathological analysis of head and neck chondrosarcoma: three case reports and literature review - Pontes, H. A. R.; Pontes, F. S. C.; de Abreu, M. C.; de Carvalho, P. L.; de Brito Kate, A. M.; Fonseca, F. P.; de Freitas Silva, B. S.; Neto, N. C. [UNESP] (Churchill Livingstone, 2012)
Chondrosarcoma (CHS) is a malignant neoplasm characterized by the formation of cartilaginous matrix by neoplastic cells, with a high propensity for local recurrences. Head and neck CHS is rare, accounting for less than 12% of all cases of CHS, usually affecting the maxilla. The majority of affected patients are in the fourth decade of life, with a slight predilection for male patients. A painless swelling is commonly the most frequent complaint. Surgery with wide en-bloc resection is the preferred treatment for CHS; radiotherapy and chemotherapy are usually palliative options. Owing to its rarity, there are few clinical series evaluating the biological behaviour of head and neck CHS. The aim of this study is to analyse the clinicopathological characteristics of head and neck CHS by reporting 3 new cases of this neoplasia affecting the jaw bones and reviewing the clinical series previously published in the English literature.
Keywords: chondrosarcoma; bone tumours; metastasis; surgery